2015
DOI: 10.1136/bmj.h706
|View full text |Cite
|
Sign up to set email alerts
|

Divorce among physicians and other healthcare professionals in the United States: analysis of census survey data

Abstract: ObjeCtives To estimate the prevalence and incidence of divorce among US physicians compared with other healthcare professionals, lawyers, and non-healthcare professionals, and to analyze factors associated with divorce among physicians. Design Main OutCOMe MeasuresLogistic models of divorce adjusted for age, sex, race, annual income, weekly hours worked, number of years since marriage, calendar year, and state of residence. Divorce outcomes included whether an individual had ever been divorced (divorce preval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 28 publications
(50 reference statements)
2
39
1
Order By: Relevance
“…A detrimental effect on social life has not been shown either. A U.S. study looking at divorce rates among physicians and other health care providers showed that it was lower than the rate in the general population ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…A detrimental effect on social life has not been shown either. A U.S. study looking at divorce rates among physicians and other health care providers showed that it was lower than the rate in the general population ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…Balance is difficult; women can feel that they are failing as a mother. Female physicians have higher divorce rates than male physicians, more notable in women who work the longest hours (7).…”
Section: Motherhood and Nephrologymentioning
confidence: 96%
“…The view by the CCE experts in this study that only chiropractors should be involved in CCEs for the establishing, monitoring and decision making of accreditation standards and processes of chiropractic education is challenged by studies in other healthcare professions [51, 52]. In a recent systematic review, only modest evidence could be found to support the importance for including medical doctors in the composition of governing bodies of healthcare organisations and hospitals [53].…”
Section: Discussionmentioning
confidence: 99%